Multiple-Antenna Multicasting Using Channel Orthogonalization and Local Refinement - Abdelkader, Ahmed; Gershman, Alex B.; Sidiropoulos, Nicholas D. (IEEE transactions on signal processing, 2010)
The problem of single-group multiple-antenna multicasting is considered, where common information should be sent to a large number of users. The multiple-antenna transmitter is assumed to accurately know the instantaneous downlink channel state information (CSI) for all users, and our objective is to design the beamformer complex weights to minimize the total transmitted power subject to individual user quality-of-service (QoS) constraints. In this correspondence, a channel orthogonalization and local refinement based approach is developed to solve this problem in an approximate way. The proposed techniques are shown via computer simulations and real data processing to offer an attractive performance-to-complexity tradeoff as compared to the state-of-the-art multiple-antenna multicasting algorithms.